Analysis of the Implementation of Grant Funds at the People's Welfare Bureau of the North Sumatra Regional Secretariat - Izusman, Izusman; Lubis, Maksum Syahri; Sembiring, Walid Musthafa (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the implementation of grant policies in the People's Welfare Bureau of the Regional Secretariat of North Sumatra Province. Through a qualitative approach, this study identifies and evaluates the process of implementing grant funds and the factors that are obstacles in its implementation. Data was obtained through in-depth interviews with government officials, grantees, and direct observation of administrative processes and related documents. The results of the study show that although the grant policy already has a clear procedure, there are still various obstacles, such as long bureaucracy, lack of transparency in the selection of recipients, weak supervision, low capacity of grant recipients in reporting, and indications of politicization of grant funds. Some of the proposed recommendations include simplifying administrative procedures, increasing transparency through open information systems, and strengthening grantee capacity in financial management and reporting. This research is expected to contribute to improving the implementation of grant policies in the future, so that it can be more effective in improving community welfare.